Age‐stratified trends in 20 years of stress incontinence surgery in Australia. (12th February 2016) - Brown, James; King, Jennifer
Abstract : Background: Stress urinary incontinence (SUI) is a common, debilitating condition in Australian women. Since its introduction in 1998–1999, the less invasive mid‐urethral sling (MUS) procedure has become the new standard for surgical correction of SUI and overall numbers of continence procedures increased. Trends since 2009 have not been analysed. Aims: To identify patterns in the surgical treatment of women with SUI in Australia from January 1994 to December 2014 stratified by age. Materials and Methods: Gender‐ and age‐specific data from Medicare Australia between January 1994 and December 2014 were extracted and the patterns of SUI surgery analysed for the 20‐year period. Data on gynaecologists and urologists performing MUS and colposuspension were collected from Department of Human Services. Results: Following the introduction of MUS, total SUI operations increased with the peak in 2002, a plateau between 2006 and 2011, and a new decline from 2012 onwards. There has been a sustained 51.7% increase in total SUI operations in 75‐ to 84‐year‐old women, and a 105.2% increase in women aged over 84. However, SUI operations in 45‐ to 64‐year‐olds decreased below pre‐MUS baseline in 2014. Conclusions: Mid‐urethral sling has become the standard SUI procedure being performed in Australia since its introduction in 1999. SUI operations have increased each year for patients aged over 65, with the greatest increase seen in patients aged over 84 – indicating expanded eligibility for SUI surgery in older women. However, since 2010, there has been a fall in SUI operations to below the pre‐MUS baseline.